Immediate behavioural responses to earthquakes in Christchurch, New Zealand, and Hitachi, Japan. Issue 1 (13th August 2015) - Lindell, Michael K.; Prater, Carla S.; Wu, Hao Che; Huang, Shih‐Kai; Johnston, David M.; Becker, Julia S.; Shiroshita, Hideyuki
Abstract : This study examines people's immediate responses to earthquakes in Christchurch, New Zealand, and Hitachi, Japan. Data collected from 257 respondents in Christchurch and 332 respondents in Hitachi revealed notable similarities between the two cities in people's emotional reactions, risk perceptions, and immediate protective actions during the events. Respondents' physical, household, and social contexts were quite similar, but Hitachi residents reported somewhat higher levels of emotional reaction and risk perception than did Christchurch residents. Contrary to the recommendations of emergency officials, the most frequent response of residents in both cities was to freeze. Christchurch residents were more likely than Hitachi residents to drop to the ground and take cover, whereas Hitachi residents were more likely than Christchurch residents to evacuate immediately the building in which they were situated. There were relatively small correlations between immediate behavioural responses and demographic characteristics, earthquake experience, and physical, social, or household context.